2014
DOI: 10.1113/expphysiol.2013.076455
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dynamic cerebral autoregulation and cerebrovascular CO2 reactivity in ageing by measurements of cerebral blood flow and cortical oxygenation

Abstract: New Findings r What is the central question in this study?It is unknown to what extent increasing age influences the dynamic adaptations of cerebral blood flow velocity and cortical oxygenation in response to changes in blood pressure (cerebral autoregulation) and to changes in carbon dioxide (cerebrovascular CO 2 reactivity). r What is the main finding and its importance?We have shown that ageing up to 86 years is associated with an overall preservation of dynamic cerebral autoregulation and cerebrovascular C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 43 publications
(131 reference statements)
8
69
4
Order By: Relevance
“…A second major outcome of this study was the observation that while healthy aging may reduce the change in CVC (that is, the dilation response), this outcome cannot be concluded from standard measures of CVR. Previously, reports on the impact of age on CVR were based primarily on mean CBFV through the MCA, 4,6,10,11 without taking into account the effect of MCA CSA. In agreement with previous studies, CVR calculated using CBFV in the current study was the same between groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second major outcome of this study was the observation that while healthy aging may reduce the change in CVC (that is, the dilation response), this outcome cannot be concluded from standard measures of CVR. Previously, reports on the impact of age on CVR were based primarily on mean CBFV through the MCA, 4,6,10,11 without taking into account the effect of MCA CSA. In agreement with previous studies, CVR calculated using CBFV in the current study was the same between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Female OA reported that they were postmenopausal (confirmed by sex hormone analysis) and not on hormone replacement therapy. Young female participants were studied in the early follicular phase of their menstrual cycle (days [1][2][3][4][5][6] or the low hormone phase of oral contraceptives (four of six young female participants were taking oral contraceptives).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The z-scores illustrated that the CVR in each patient, at least in some region, was substantially distinct from that of any of the healthy subjects regardless of the sex and age distribution. 42 This suggests that the z-map analysis may also be used to identify abnormalities of CVR in a number of other neurologic diseases.…”
Section: Limitationsmentioning
confidence: 99%
“…Cerebral autoregulation (CA) characterizes the efficiency in maintaining CBF despite changes in arterial blood pressure (ABP) (48) and is commonly assessed by the change in cerebrovascular resistance (CVR) for a given change in pressure (21,26,48). When considering CVR as the solitary regulator (i.e., CVR ϭ ABP/CBF), CA has proven to be a robust physiological trait, resistant to aging (12,14,26,34) and hypertensive pathology (12,45,53).The definition of CA has been dichotomized as "dynamic," involving rapid changes in pressure (25, 54), and "static," involving steady-state changes over the course of minutes or longer (48). Both definitions of CA, however, are characterized by the relationship between mean flow and pressure, averaged across one or more cardiac cycles.…”
mentioning
confidence: 99%